Imagery rescripting as an adjunct clinical intervention for obsessive compulsive disorder. (August 2019) - Maloney, Gayle; Koh, Gennifer; Roberts, Stephen; Pittenger, Christopher
Highlights: Imagery rescripting was found to be an effective treatment adjunct for OCD. 12 out of 13 patients reported ≥35% improvement in Y-BOCS following treatment. 6 patients achieved clinically significant change following a single session. The remaining 6 patients required between 2–5 imagery rescripting sessions. Lower baseline Y-BOCS predicted improvement after one imagery rescripting session. Abstract: Novel adjunct psychological techniques are needed for the large number of patients with OCD who remain symptomatic despite the effective implementation of standard evidence-based treatments. The aim of this study was to examine the efficacy of imagery rescripting (ImRs), an established technique for the treatment of traumatic stress, as a treatment for OCD symptoms that were not responsive to standard exposure and response prevention (ERP). Thirteen patients completed a baseline assessment followed by a control intervention that involved discussion of an aversive memory linked with the onset of OCD symptoms. Treatment then involved provision of 1–6 ImRs sessions; ImRs continued until patients achieved a 35% reduction in symptoms, as measured using the Y-BOCS one week after each treatment. Patients were followed up one and three months after the treatment completion. Twelve out of thirteen patients achieved ≥35% improvement in Y-BOCS. Of these patients, six required only a single ImRs session, while the remaining six patients required 2–5 ImRs sessions to achieve a clinically significant change. Lower baseline Y-BOCS predicted improvement after a single treatment session. ImRs may be a useful adjunct for treatment-resistant OCD associated with past aversive experiences, especially when symptomatology remains within the mild-moderate range after standard ERP.